De-amortization of Algorithms - Rao Kosaraju, S.; M. Pop (Computing and CombinatoricsComputing and Combinatorics, 1998)
De-amortization aims to convert algorithms with excellent overall speed, f ( n ) for performing n operations, into algorithms that take no more than O ( f ( n )/ n ) steps for each operation. The paper reviews several existing techniques for de-amortization of algorithms.